NILAI-NILAI PENDIDIKAN YANG TERKANDUNG DALAM QS. AN-NAHL AYAT 106 DAN QS. AZ-ZUMAR AYAT 9 - Saputra, Muhammad Rohan; Wardan, Khusnul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Islamic education aims to shape individuals who are faithful, knowledgeable, and virtuous, yet the reality in the field still shows a gap between the ideal goals and actual practices. Students are often weak in integrity, have low learning motivation, and perform worship merely as a routine. This study focuses on the educational values contained in QS. An-Nahl verse 106 and QS. Az-Zumar verse 9, namely steadfast faith, sincerity of heart, the importance of knowledge, and sincerity in worship. This research employed a literature study method by collecting and analyzing sources from books, Qur’anic exegesis, and relevant scientific articles. The analysis was conducted by examining the Ministry of Religious Affairs’ interpretation and Quraish Shihab’s Tafsir Al-Mishbah to obtain both philosophical and applicative understandings of the verses. The findings reveal that QS. An-Nahl verse 106 emphasizes steadfast faith and sincerity of heart as the foundation of religious character, while QS. Az-Zumar verse 9 stresses the importance of knowledge and sincerity in worship as the basis of forming a complete Muslim personality. This study concludes that integrating Qur’anic values into Islamic education can strengthen students’ cognitive, affective, and spiritual aspects. The prospect of this research lies in its application to the curriculum, learning strategies, teacher role modeling, and habituation programs to produce a religious, intelligent, honest, and sincere generation capable of facing global challenges. ABSTRAKPendidikan Islam bertujuan membentuk manusia yang beriman, berilmu, dan berakhlak mulia, namun realitas di lapangan menunjukkan adanya kesenjangan antara tujuan ideal dan praktik nyata. Peserta didik masih sering lemah dalam integritas, rendah motivasi belajar, serta menjalankan ibadah sebatas rutinitas. Penelitian ini berfokus pada nilai-nilai pendidikan yang terkandung dalam QS. An-Nahl ayat 106 dan QS. Az-Zumar ayat 9, yaitu keteguhan iman, kejujuran hati, pentingnya ilmu, dan keikhlasan ibadah. Penelitian menggunakan metode studi literatur dengan menghimpun dan menganalisis sumber dari buku, tafsir, dan artikel ilmiah yang relevan. Analisis dilakukan dengan mengkaji tafsir Kemenag dan Tafsir Al-Mishbah untuk memperoleh pemahaman filosofis sekaligus aplikatif terhadap ayat-ayat tersebut. Hasil penelitian menunjukkan bahwa QS. An-Nahl ayat 106 menekankan keteguhan iman dan kejujuran hati sebagai fondasi karakter religius, sedangkan QS. Az-Zumar ayat 9 menegaskan keutamaan ilmu dan keikhlasan ibadah sebagai dasar pembentukan pribadi muslim yang utuh. Penelitian ini menyimpulkan bahwa integrasi nilai Qur’ani ke dalam pendidikan Islam dapat memperkuat aspek kognitif, afektif, dan spiritual peserta didik. Prospek pengembangan penelitian ini adalah penerapannya dalam kurikulum, strategi pembelajaran, keteladanan guru, dan program pembiasaan sehingga dapat melahirkan generasi yang religius, cerdas, jujur, dan ikhlas dalam menghadapi tantangan global.